Features of formation and implementation of state policy for economic development of territorial communities in the regions of Ukraine - Tereshchenko, Tetiana (Theory and Practice of Public Administration, 2026)
The article examines the features of the formation and implementation of the state policy of economic development of territorial communities in the regions of Ukraine in modern conditions. The research methodology is based on systemic and comprehensive approaches, a synthesis of modern scientific research and is a combination of systemic, institutional and comparative approaches, which made it possible to consider the state policy of economic development of territorial communities at the regional level as a holistic system, vulnerable to destructive influences and existing threats.It is noted that the formation and implementation of an effective state policy of economic development of territorial communities requires deep regional differentiation of state support instruments, integration of humanitarian and economic measures, as well as innovative mechanisms for attracting investments under existing risks. Key problems and prospects for improving the state policy of economic development of territorial communities at the regional level in Ukraine are identified, taking into account existing challenges and threats. The need for more flexible public management approaches in the formation and implementation of the state policy of economic development of territorial communities in different regions of Ukraine in modern conditions is proven, which, among other things, should be aimed at strengthening the security component.The directions for increasing the effectiveness of the state policy of economic development of territorial communities in the regions of Ukraine are determined on the basis of a differentiated approach, i.e. combining a nationwide strategic framework with flexible local adaptation by ensuring: strengthening the financial self-sufficiency of communities through the modernization of the system of inter-budgetary relations; developing public-private partnership instruments for the implementation of local projects; supporting the institutional potential of local governments; introducing innovative risk management mechanisms and planning for the restoration of territories. Based on the analysis of scientific approaches and practical results of state regional policy, directions for modernization of the state policy of economic development of territorial communities are proposed, namely: improving financial instruments; developing inter-municipal cooperation; strengthening institutional capacity; expanding the participation of the private sector; scaling up local successful public management practices.Prospects for further research are outlined related to the development of integrated models of public policy that would ensure a balance between investment, control and security in matters of economic development of territorial communities in the regions of Ukraine.